Tumor suppressor ZHX2 inhibits NAFLD–HCC progression via blocking LPL-mediated lipid uptake - Wu, Zhuanchang (Cell Death Differ, 2019)
Non-alcoholic fatty liver disease (NAFLD) leads to hepatocellular carcinoma (HCC). However, the underlying mechanism remains largely unclear. Here, we investigated the role of the tumor suppressor Zinc fingers and homeoboxes 2 (ZHX2) in the progression of NAFLD to HCC. ZHX2 expression was significantly decreased in fatty liver tissues, especially in the liver with NAFLD–HCC. ZHX2 overexpression disturbed lipid homeostasis of cultured HCC cells, and inhibited lipid deposition in hepatocytes both in vitro and in vivo. Moreover, ZHX2 inhibited uptake of exogenous lipids through transcriptional suppression of lipid lipase (LPL), leading to retarded proliferation of HCC cells. Importantly, LPL overexpression significantly reversed ZHX2-mediated inhibition of HCC cell proliferation, xenograft tumor growth, lipid deposition, and spontaneous liver tumor formation. Consistently, IHC staining demonstrated a negative correlation of ZHX2 with LPL in an HCC cohort. Collectively, ZHX2 protects hepatocytes from abnormal lipid deposition in NAFLD through transcriptional repression of LPL, which subsequently retards cell growth and NAFLD–HCC progression. These findings illustrate a novel mechanism of NAFLD progression into HCC.